1982
DOI: 10.1159/000283940
|View full text |Cite
|
Sign up to set email alerts
|

Familially Accumulated Schizophrenia (Folie à Cinq) in Association with Stein-Leventhal Syndrome

Abstract: The authors describe the psychosis of both parents and their three daughters. The psychosis of the father and three daughters corresponds to the paranoid schizophrenias (more specifically, the affective paraphrenias), while the mother’s psychosis is largely the result of induction. All 3 daughters suffer from surgically confirmed Stein-Leventhal syndrome. Such a close association of the two diseases cannot be by chance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…She suddenly became confused, excited, and walked around at night one day around ovulation. She was admitted to hospital, and [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] mg/day of haloperidol was administered as treatment, but her excitation persisted. She said that she was being looked at by all people in the world.…”
Section: Casementioning
confidence: 99%
“…She suddenly became confused, excited, and walked around at night one day around ovulation. She was admitted to hospital, and [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50] mg/day of haloperidol was administered as treatment, but her excitation persisted. She said that she was being looked at by all people in the world.…”
Section: Casementioning
confidence: 99%
“…Shared psychotic disorder is usually “Folie à deux” (delusions shared by two individuals) [ 1 , 2 ] or more rarely “Folie à trois” [ 3 ], while “Folie à quatre” and delusions shared by more than four individuals are extremely rare. Indeed, only a few cases of “Folie à quatre” [ 4 6 ] and “Folie à cinq” [ 7 , 8 ] have been reported. In recent years, we are aware of only one such case of “Folie à quatre” in Japan [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…By means of a health questionnaire study, Orenstein et al (1986) suggested an association between POD and Briquet's syndrome, and found that patients with POD report significantly more psychological and physical complaints than normal controls. Petho et al (1982) described a family in which paranoid schizophrenia was diagnosed in both parents and their three daughters. All the daughters suffered from POD.…”
Section: Introductionmentioning
confidence: 99%